An Assessment of Wheat Procurement Issues in Jafferabad District of Balochistan - Parvez A. Rind; Abdul Latif Bhutto; Rafique A. Chandio; Khalid N. Panhwar; Aijaz A. Khooharo (Journal of Basic & Applied Sciences, 2014)
Exploitation of farmers’ profit margins by middlemen is well documented and reported by various studies. In this regard, public sector initiated support price and procurement policies especially for wheat. Presently, Pakistan Agricultural Storage and Services Corporation (PASSCO) is a key procurement agency in Pakistan. It has been reported that in certain cases, PASSCO do not reach directly to farmers for the purchase of wheat. Hence, the role of middlemen in procurement of wheat is once again emerging and leaving low profit margins for the farmers. In this regard, this study aimed to assess wheat procurement issues in Jaffarabad district of Balochistan. Quite a large majority of the respondents were aware about seed dealers (69.4%), whole sellers (66.6%) and commission agents (62.5%). On the other hand, majority (55.5%) of the respondents were not aware about procurement centers of PASSCO. Price variation by various wheat procurement agencies was observed from Rs. 22.50kg-1 offered by seed dealer to Rs. 31.25 kg-1 offered by PASSCO. One fourth (25.0%) of the respondents opted “lack availability of gunny bags” as one of the top most problem in selling wheat while 20.8% respondents reported for timely availability (especially during harvesting season) of gunny bags as a serious problem. Lack of coordination was reported by 13.8% while the same proportion of the respondents was of the opinion “delay in announcement of the support price” is one of the most important issues. Majority (94.44%) of the farmers suggested that the transport facilities should be provided to farming community for transport of their wheat from farm to market.